تطـور حركية التعليم في الجزائر من عام 1830 إلى عام 1990 - عبد العزيز, محي الدين (دفـاتر المـــــــــــخبـر, 2018)
ملخص: مرت حركية التعليم في الجزائر بعدة مراحل أساسية، تكونت خلالها المدرسة الجزائرية، ,واكتسبت بسبب المشكلة الاستعمارية، كبقية بلدان المغرب العربي، صبغة خاصة للمدرسة الجزائرية، جعلت هم المدرسة منصبا في جل الاهتمامات إلى التحرر من الهيمنة الثقافية الاستعمارية، وهو ما أدى إلى إعادة الصياغة التصورية للمدرسة الجزائرية بمقتضى الإصلاح الجذري سنة 1976، إلا أنه اصطدم بظروف واقعية أفرزت العديد من المشكلات سواء ارتبطت بمسار الإصلاح ذاته، أم بأزمات على المستوى الاقتصادي والسياسي، أدت إلى التأجيل، والتخلي عن بعض تلك التصورات، وهو ما ظهر من خلال التعديلات المتواصلة طيلة الفترة ما بعد تعميم المدرسة الأساسية، وإلى غاية الشروع في تطبيق المشروع الإصلاحي الجديد 2003/2004، والذي يعد من وجهة نظر بعض الإصلاحيين حلقة موالية من حلقات إصلاح1976 الجذري، وهو لا يخرج عن صلبه، حسب البعض، وعودة إلى عهد الازدواجية وفرسنة التعليم. Abstract: The Algerian educational movement has gone through many essential stages during which the Algerian school has been shaped.  Even if these stages do not differ in form compared to what is found in the other societies, the problem of colonization in north Africa in general, and in Algeria in specific has given  special characteristics to the Algerian school.  This has made getting rid of the cultural dependence the first concern of the Algerian school. It has also led to the reconsideration of its conception in the 1976 radical reform. However , the new conception has met many obstacles which gave birth to a series of problems related to the reform itself or at the political and economic levels. This situation has either caused postponing the reform , or neglecting parts of the conception. This has appeared through the continuous changes during the period coming just after the generalization of the fundamental school, and which continued until the application of the 2002-2004 reform project. The latter is considered by some reformists as an integrated part of the 1976  radical reform which represents a return to the era of bilingualism and reintroduction of the French aspect into education.